A new approach in individual tree counting of Nyatoh (Palaquium spp.) using an airborne spectroradiometer - Jusoff, Kamaruzaman (Science Publications, 2010)
Problem statement: In Malaysia inadequate data are available to make decisions regarding the sustainable management of Nyatoh (Palaquium spp.). Factual data and estimation of Nyatoh in the lowland dipterocarp forest resources are still lacking or, if available, are not complete, reliable or up to date. The collection and compilation of information and updating of existing data in near real time is a priority. Nyatoh is one of the important and popular timber species for furniture, solid doors and planks. Approach: In order to determine Nyatoh's latest species count in the Federal Territory (FT)'s Permanent Reserved Forest, a study on the distribution of Nyatoh in Bukit Nanas Forest Reserve (FR), FT was conducted using an airborne hyperspectral remote sensing technique with an objective to identify, count and map the species of Nyatoh in Bukit Nanas FR, FT. A False Color Composite (FCC) airborne hyperspectral image of the study area was used with a Sobel 3Ã—3 filter and Spectral Angle Mapper (SAM) to classify and separated the individual Nyatoh from other tree species within Bukit Nanas FR. Results: A thematic map of individual Nyatoh spatial distribution in Bukit Nanas FR was developed showing a total of 36 individual Nyatoh trees in a 2.7 h study plot. There were 34 trees confirmed available on the ground with a mapping accuracy of 94.4%. Conclusion: The AISA airborne spectroradiometer data is capable of mapping and counting individual tropical timber trees especially Palaquium spp. with an acceptable accuracy of more than 90%. However, in order to improve the mapping accuracy, it is recommended that a higher spatial resolution image data is necessary in addition to a higher precision field GPS usage. This approach may be well integrated in the GIS-based decision support system to better manage and conserve such depleting timber species in the FT's state land and permanent reserved forests.